The two faces of Interleukin-17A in atherosclerosis - Akhavanpoor, Mohammadreza; Akhavanpoor, Hamidreza; Gleißner, Christian A.; Wangler, Susanne; Dösch, Andreas; Katus, Hugo; Erbel, Christian (Current drug targets, 2017)
A complex network of different cytokines and chemokines modulates atherosclerosis, a chronic inflammatory disease. Interleukin-17A (IL-17A) is expressed by different leukocyte subsets such as CD4+IL-17+ T cells (Th17), γδ T cells, natural killer cells, natural killer T cells, and neutrophils. IL-17A plays an important role in host defense and is involved in the pathology of different autoimmune and inflammatory diseases. Recent studies demonstrate an association of IL-17A with atherosclerosis. IL-17A seems to have primarily pro-inflammatory effects in atherogenesis, although there are partially controversial results in the literature. In the murine system, several studies indicate a pro-atherogenic role of IL-17A mediated by increased migration of leukocytes (especially macrophages) into atherosclerotic lesions, increased expression of pro-inflammatory cytokines and chemokines as well as plaque destabilizing matrix-metalloproteinases using Apoe-/- and LDLr-/- mice. In contrast, three studies show atheroprotective effects of IL-17A mediated by downregulation of aortic VCAM-1 expression on endothelial cells and increased collagen production by vascular smooth muscle cells (VSMCs) in LDLr-/- mice. In humans, expression of IL-17A was associated with increased inflammation and plaque vulnerability in human atherosclerotic lesions. Moreover, IL-17A induced a pro-inflammatory, pro-thrombotic, plaque-destabilizing, and cell-attracting response of the inflammatory milieu of human plaque tissue samples. Notably, a recently published study challenged these findings by showing a worse outcome of patients with acute myocardial infarction with low serum levels of IL-17A. In the following review, we will focus on the recent progress of functional studies of IL-17A in atherosclerosis and will try to collect explanations for the controversial data.
Gesehen am 09.04.2018